Less public investment due to an aging population - Philipp Jäger (RWI - Leibniz-Institut für Wirtschaftsforschung, 2016)
The constant decline in public investment over the last four decades can only partly be explained by high public debt. - Public investment, for instance in infrastructure, has been constantly decreasing for four decades. New research by RWI for 13 OECD-countries shows: this development significantly correlates with population aging. Senior citizens do not value future payoffs of infrastructure projects and other public investments as much as working-age-individuals since people's time preferences change with age. Because of their growing voting power, elderly voters exhibit an increasing influence on policy proposals of political parties. To counter these effects, politicians should consider demeny voting, where parents get additional votes for each child. Other options include user-pay-infrastructure or alternative funding sources like Public Private Partnerships.
Keywords: 330